Customer participation in firm-initiated activities via social media: Understanding the role of experiential value. Issue 2 (May 2021) - Quach, Sara; Shao, Wei; Ross, Mitchell; Thaichon, Park
This study aims to examine the effects of experiential value in firm-initiated social media activities on brand attitude and purchase engagement. An online survey with the experimental design was used to collect data from 181 social media users who were over 18 years old. The results of this study showed that experiential value positively influenced both brand attitude and purchase engagement. In addition, brand attitude mediated the relationship between experiential value and purchase engagement. The most significant effects of experiential value on brand attitude and purchase engagement were observed at the medium level of participation required in the activity. It was also revealed that the more privacy concern customers had, the stronger the effect of experiential value on brand attitude became. In contrast, as privacy concern increased, the impact of experiential value on purchase engagement decreased. The study extends the current understanding of customer experience and provides important managerial implications.